Development of products with herbal isolates for cutaneous application - Žugić, Ana (Archives of Pharmacy, 2022)
When developing products with herbal isolates/herbal drug preparations, aside safety and efficacy demands, specific quality requirements should be satisfied, which is very complex due to compounded chemical composition of herbal isolates (among other tests, identification and quantification of appropriate substances and their stability should be assessed). Also, when these products are intended for cutaneous application, it is very important that they are aesthetically acceptable for users after usage and therefore, during development, special attention should be paid to their satisfactory sensory characteristics. As example of development of product with herbal drug preparations for cutaneous application, preformulation and formulation studies of Usnea barbata extract in alkyl polyglucoside-based emulsion potentially used for skin infections is presented. Preformulation studies of extract served to design two protocols for incorporating its three different concentrations into carrier, after which comprehensive assessment of colloidal structure, physical stability and biopharmaceutical characteristics of prototype formulation of final product was performed. Assessment of skin effects and safety of this product were obtained in in vivo measurements of biophysical parameters of skin using different experimental protocols. Same measurements were used in investigation of skin effects of other products with plant isolates (fatty seed oil and leaf extract of blueberry, Vaccinium myrtillus/fatty seed oil of hemp, Cannabis sativa and flower extract of immortelle, Helichrysum italicum), which were supplemented by sensory characteristics assessment. Obtained results indicated importance of appropriate vehicle/carrier selection and plant isolates incorporation method on their release/availability, as well as on colloidal structure, sensory properties and skin effects of final products.